TEACHING EARLY CHILDHOOD TO BE HEALTHY AND CLEAN IN EVERYDAY LIFE - Daviq Chairilsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Living healthily and cleanly is somethimes neglected by parents and teachers to be taught in a program and a sustainable manner. Teachers assume that parents have taught hygiene and healthy living habits at home, even though it is not clear whether every parent understands the proper way to live healthily and cleanly in early childhood. Parents feel that teachers must have taught this clean and healthy lifestyle while studying at school. Indeed, teachers are more preoccupied with children's learning achievement that is more of academic knowledge. Utilizing literature study method, this article aims to help teachers about the importance and the implementation of a clean and healthy lifestyle in early childhood. The role of kindergarten teachers is to stimulate character education for a healthy and clean living that should be a priority in all aspects of learning. A clean and healthy lifestyle can be applied at schools through: 1) instilling values for a clean and healthy lifestyle at schools through health education, 2) carrying out extracurricular activities with clean and healthy life behavior values for students, 3) conducting a counseling and working together with the goverenment health office.